Transcriptomic analysis of rapeseed (Brassica napus. L.) seed development in Xiangride, Qinghai Plateau, reveals how its special eco-environment results in high yield in high-altitude areas - Xiong, Huiyan; Wang, Ruisheng; Jia, Xianqing; Sun, Hezhe; Duan, Ruijun (Frontiers in Plant Science, 2022)
As one of the most important oil crops, rapeseed (Brassica napus) is cultivated worldwide to produce vegetable oil, animal feed, and biodiesel. As the population grows and the need for renewable energy increases, the breeding and cultivation of high-yield rapeseed varieties have become a top priorities. The formation of a high rapeseed yield is so complex because it is influenced not only by genetic mechanisms but also by many environmental conditions, such as climatic conditions and different farming practices. Interestingly, many high-yield areas are located in special eco-environments, for example, in the high-altitude Xiangride area of the Qinghai Plateau. However, the molecular mechanisms underlying the formation of high yields in such a special eco-environment area remain largely unknown. Here, we conducted field yield analysis and transcriptome analysis in the Xiangride area. Compared with the yield and environmental factors in the Xinning area (a low-yielding area), we found that the the relatively longer daylight length is the key to high rapeseed yield in the Xiangride area, which leads to an up to 52.1% increase in rapeseed yield, especially the increase in thousand seed weight and silique number. Combined with transcriptome H-cluster analysis and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional analysis, we can assume that the grain development of rapeseed in the Xiangride area is ahead of schedule and lasts for a long time, leading to the high-yield results in the Xiangride area, confirmed by the expression analysis by quantitative real-time polymerase chain reaction (qRT-PCR) of yield-related genes. Our results provide valuable information for further exploring the molecular mechanism underlying high yield in special ecological environments and provide a helpful reference for studying seed development characteristics in special-producing regions for Brassica napus.